Karakteristik Kepribadian, Harga Diri dan Gaya Hidup Hedonisme Pada Mahasiswa Konsumen Starbucks - Teguh Lesmana; Rudy Santoso (Jurnal Ilmu Perilaku, 2019)
Coffee consumption of Indonesian people tends to increase over the past few years. Coffee drinking activity now tends to be a lifestyle where someone can spend time having fun. The purpose of this study was to determine the relationship between personality traits and self-esteem with hedonistic lifestyle on Starbucks consumer in Jakarta. The participants in this study consisted of 390 students who had visited Starbucks. Research participants were asked to fill out the Big Five Inventory-10 (BFI-10) questionnaire and Rosenberg self-esteem scale questionnaire that had been adapted to Indonesian, as well as the scale of the hedonistic lifestyle. The results showed that there was a significant negative relationship between self-esteem and hedonistic lifestyle, while conscientiousness personality traits had a significant positive relationship with the hedonistic lifestyle. This result explains that students can have a Hedonistic lifestyle when they do not have a positive assessment of themselves. The result of a significant positive relationship between conscientiousness personality and hedonistic lifestyle is in line with the results of previous studies which found a significant relationship between conscientiousness personality and caffeine consumption. Thus the tendency of coffee consumption based on the hedonism lifestyle is likely to be influenced by self-esteem and personality possessed.